The Relationship Between Constant and Spring Stretch in Hooke's Law Material Using Virtual Lab (PhET) - Budiman, Arief; Nufus, Ayu Tazkyatun; Moenore, Dian Morika; Rustiani, Eka Astria (Jurnal Materi dan Pembelajaran Fisika, 2024)
This study aims to analyze the relationship between spring constant and spring stretch using Virtual Lab (PhET). The method used in this study is an experimental method that allows testing hypotheses or theories through the control of certain variables to understand the cause-and-effect relationship between independent and dependent variables. The independent variable in this study is the mass that is changed to affect the spring, while the dependent variable is the change in the position of the spring and the force produced. The simulation was carried out using PheT learning media. The first thing to do is to vary the mass. Then you will get the result of increasing the length for each mass. After that, the data that has been obtained is analyzed to determine the spring coefficient. Based on these simulations, it can be concluded that a spring's elasticity level influences the stretching level that occurs after a spring is treated in the form of varying masses.